Evaluación Del Impacto De La Política Pública “Programa De Estímulos A La Innovación”, En El Contexto De Propiedad Industrial En México - Antonio Solís Lima; María Catalina Ovando Chico; Emmanuel Olivera Pérez; Miguel Ángel Rodríguez Lozada (European Scientific Journal, ESJ, 2018)
In order to trigger economic and technological development in Mexico, the government of this country is trying different ways to boost innovation. One of them is through the public policy "Program of Stimuli for Innovation (PSI)". This consists of granting subsidies to companies for the development and commercialization of technological innovations that trigger new markets. However, although annual reports of the PSI management have been generated, studies conducted to evaluate this program in terms of industrial property appropriation are still unknown. For the foregoing, the object of this studywas to evaluate the PSI to know its national impact in terms of appropriation of industrial property in the period 2009-2016. The evaluation consisted of making a quantitative, statistical, descriptive and inferential analysis of the PSI, using databases generated by Mexican public institutions. The results of this research showed that although the PSI grants motivated the link between research centers and companies for the development of innovative technologies, the appropriation of industrial property managed by Mexicans was modest. Likewise, it was found that the grants were not granted in an equitable manner to the different types of companies that participated in the program. Concluding that it is necessary to evaluate and supervise this public policy with objective indicators that allow it to be more effective. It is expected that this study will contribute to making a proposal for improvement to this public policy that contributes to the economic and technological growth of this country.